The development and validation of the principal innovation leadership scale in Malaysian secondary schools - Dayang Rafidah Syariff M. Fuad; Khalip Musa; Hamidah Yusof; Zahari Hashim (Institute of Advanced Engineering and Science, 2022)
Scholars used multiple variables in measuring innovation leadership due to the differences in concept and understanding of this leadership in different fields. We develop the instrument to fill in the gaps in academicians’ and scholars’ assessments pertaining to the concept of innovation leadership, especially in the sense of education. This paper aims to explain the instrument development and validation process of the face and content validity for the purposed dimensions and items. All the constructs were generated through a rigorous review of the literature. There were six experts involved in validating the face and content validity of this instrument. Content validity index (CVI) and Modified Kappa statistics were used. The cut-off point of all items was 0.8 which retained as a final instrument. Therefore, from the 58 items, four were deleted as it is not reached the level of agreement between all the experts. The final instruments for further validation consisted of 54 items which fell under eight dimensions, namely: i) Creative behavior; ii) Ideal influence; iii) Effective communication; iv) Empowerment and mentoring; v) Technical skills; vi) Entrepreneurship; vii) Opening behavior; and viii) Closing behavior were identified. Therefore, this instrument could be utilized for further validation.